2020
DOI: 10.21037/tau.2020.03.13
|View full text |Cite
|
Sign up to set email alerts
|

Tumor heterogeneity in muscle-invasive bladder cancer

Abstract: Muscle-invasive bladder cancer (MIBC), a highly heterogeneous disease, shows genomic instability and a high mutation rate. Clinical outcomes are variable and responses to conventional chemotherapy differ among patients (due to inter-patient tumor heterogeneity and inter-tumor heterogeneity) and even within each individual tumor (intra-tumor heterogeneity). Emerging evidence indicates that tumor heterogeneity may play an important role in cancer progression, resistance to therapy, and metastasis. Comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 108 publications
(155 reference statements)
1
6
0
Order By: Relevance
“…There are new proposals of panels and groups of biomarkers to identify bladder cancer subtypes, with state-of-the-art technology. Kang et al, 2020 also illustrate the taxonomic classifications, with suggested treatments for different MIBC subtypes based on molecular biomarkers [109]. The combination of neoadjuvant therapy with immune checkpoint inhibitors (designed for suitable biomarker expression) is currently being tested and is expected to increase efficacy in treatments [110].…”
Section: Bladder Cancer Therapiesmentioning
confidence: 99%
“…There are new proposals of panels and groups of biomarkers to identify bladder cancer subtypes, with state-of-the-art technology. Kang et al, 2020 also illustrate the taxonomic classifications, with suggested treatments for different MIBC subtypes based on molecular biomarkers [109]. The combination of neoadjuvant therapy with immune checkpoint inhibitors (designed for suitable biomarker expression) is currently being tested and is expected to increase efficacy in treatments [110].…”
Section: Bladder Cancer Therapiesmentioning
confidence: 99%
“…However, this is not the case with biopsy samples. Here, the ability of Jacalin to distinguish between normal, Ta and T1 tumours is undetectable, presumably due to the differences between patients and within the tumour (Kang et al 2020). Furthermore, T24 and RT4 cells differ from NPU cells in that they bind signi cantly less DSA.…”
Section: Discussionmentioning
confidence: 95%
“…The recurrent nature of bladder tumors, the availability of matched transurethral resection and cystectomy specimens, exfoliated urothelial cells, and the ease of assaying free-circulating DNA, transcripts, and soluble proteins/metabolites in urine have all enabled such investigations. These studies have certainly advanced knowledge about the biology of bladder tumors, but their goal has been the promise of personalized medicine; specifically, molecular tests to predict outcome and response to intravesical, neoadjuvant and adjuvant/salvage treatments and to guide targeted treatment selection [ 7 , 20 , 28 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Molecular Basis Of Bc and Clinical Translationmentioning
confidence: 99%